2008
DOI: 10.1128/iai.01484-07
|View full text |Cite
|
Sign up to set email alerts
|

Intravaginal Immunization of Mice with Recombinant Salmonella enterica Serovar Typhimurium Expressing Human Papillomavirus Type 16 Antigens as a Potential Route of Vaccination against Cervical Cancer

Abstract: Cervical cancer, the second leading cause of cancer deaths in women, is the consequence of high-risk human papillomavirus (HPV) infections. Toward the development of therapeutic vaccines that can induce both innate and adaptive mucosal immune responses, we analyzed intravaginal (ivag) vaccine delivery of live attenuated Salmonella enterica serovar Typhimurium expressing HPV16L1 as a model antigen. Innate immune responses were examined in cervicovaginal tissues by determining gene expression patterns by microar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 71 publications
2
35
0
Order By: Relevance
“…A previous study reported an upregulation in both IL-1 and IFN-␥ mRNAs in the Peyer's patches and mesenteric lymph nodes in mice following immunization with attenuated Salmonella constructs at day 7 (23). Similarly, Echchannaoui et al (12) showed that a wide range of genes, including those for chemokines and Th1-and Th2-type cytokines, were upregulated in mice immunized with live attenuated recombinant S. Typhimurium strains compared to control mice at day 1. In contrast, Trebichavsky et al (46) found that attenuated aroA S. Typhimurium did not induce IL-1␤, IL-18, TNF-␣, or IFN-␥ in the ileum and plasma in gnotobiotic pigs at 24 h after the infection.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported an upregulation in both IL-1 and IFN-␥ mRNAs in the Peyer's patches and mesenteric lymph nodes in mice following immunization with attenuated Salmonella constructs at day 7 (23). Similarly, Echchannaoui et al (12) showed that a wide range of genes, including those for chemokines and Th1-and Th2-type cytokines, were upregulated in mice immunized with live attenuated recombinant S. Typhimurium strains compared to control mice at day 1. In contrast, Trebichavsky et al (46) found that attenuated aroA S. Typhimurium did not induce IL-1␤, IL-18, TNF-␣, or IFN-␥ in the ileum and plasma in gnotobiotic pigs at 24 h after the infection.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the immunization regimen, stool samples were collected on days 0, 2,4,7,9,11,14,28,30,32,34,49,51,53, and 55 to determine the viability of L. plantarum and its ability to colonize the digestive tract. Suspensions of stools collected from mice immunized with LpA or LpA␣ contained on average 10 6 cells/g of luminal contents, in contrast to the control.…”
Section: Resultsmentioning
confidence: 99%
“…Mucosal vaccines using commensal bacteria rely on its endogenous regulation being transferred to the vaccine antigen (40). Vaccines based on attenuated bacterial pathogens, especially live Salmonellabased oral vaccines, have demonstrated the ability to induce protective mucosal and systemic immune responses (6,14,52,61,63). However, public fear of using an attenuated pathogen as a vaccine carrier has deterred its acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been clearly established that the use of attenuated Salmonella strains as live oral vaccines is a safe and effective means of inducing significant humoral and secretory antibody responses in animal species, including humans and mice (8,16,21,(32)(33)(34). The use of plasmid-based expression systems to elevate foreign antigen levels in Salmonella live vaccine vectors is ideal, but these systems have the serious disadvantages of instability and selective requirements in vivo (10,14,17,38).…”
mentioning
confidence: 99%